Climatic influences on southern makassar strait salinity over the past century - Murty, Sujata Annavarapu (2018)
The Indonesian Throughflow (ITF) is a globally important ocean current that fuels heat and buoyancy fluxes throughout the Indo‐Pacific and is known to covary in strength with the El Niño Southern Oscillation at interannual time scales. A climate system with a less well‐quantified impact on the ITF is the East Asian Winter Monsoon (EAWM), which drives less saline surface waters from the South China Sea (SCS) into the Makassar Strait, obstructing surface ITF flow. We present a subannually resolved record of sea surface salinity (SSS) from 1927 to 2011 based on coral δ18O from the Makassar Strait that reveals variability in the relative contributions of different source waters to the surface waters of the Makassar Strait during the boreal winter monsoon. We find that the EAWM (January–March) strongly influences interannual SSS variability during boreal winter over the twentieth century (r = 0.54, p << 0.0001), impacting surface water circulation in the SCS and Indonesian Seas.